The Tranvieri Gym Young Immigrant Boxers in the Neighborhood Bolognina (Global Journal of Human-Social Science, 2016)
The paper describes the social organization of boxing gym "Tranvieri", located in Bolognina, a working class neighbourhood in the city of Bologna which has been rapidly changing over the last twenty years due to the closing of factories and the arrival of immigrants, especially from Maghreb. The gym population has changed accordingly: currently about two thirds of those attending the gym as a leisure centre are children of immigrants. I studied the practices of everyday life by these young boxers born in Italy but without citizenship who daily frequent this gym once finished vocational school, work, family responsibilities. Boxing is for them not a solution to the frustration inflicted by a social world they perceive as indifferent if not hostile towards them, rather the possibility of not being represented in it as excluded people.
Keywords: urban space; boxing; young immigrants; neighborhood; ethnography